Chloroplast genome characteristics and phylogenetic analysis of Macropanax rosthornii (Harms) C.Y. Wu ex G. Hoo (Araliaceae) - Shuxin Du; Huiying Huang; Shuhui Yang; Tianyi Gu; Mengli Zhou; Ruihong Wang (Mitochondrial DNA. Part B. Resources)
Macropanax rosthornii (Harms) C.Y.Wu ex G.Hoo 1900 is a small tree or evergreen shrub of the family Araliaceae, mainly distributed in southern China and Vietnam with a small distribution area. M. rosthornii is a kind of high-quality wild ornamental plant resource and is also known for its effective medicinal treatment for fracture, rheumatoid arthritis, traumatic injury, infant malnutrition, etc. In this study, the first complete chloroplast genome of M. rosthornii was reported and phylogenetic analysis was conducted with other 10 species from Araliaceae. The chloroplast genome was 152,831 bp with 39% overall GC content and includes a large single-copy (LSC) region (93,751 bp), a small single-copy (SSC) region (18,930 bp), and a pair of inverted repeats (IR) regions (20,075 bp). There are 109 genes in the chloroplast genome of M. rosthornii, including 78 protein-coding genes, 21 tRNA genes, and 10 rRNA genes. The phylogenetic tree showed that M. rosthornii is closely related to Hydrocotyle vulgaris and Hydrocotyle sibthorpioides. The chloroplast genome reported here will be beneficial for its interspecific identification and evolutionary studies of Macropanax.